Biomaterials: Disordered Topography Mediates Filopodial Extension and Morphology of Cells on Stiff Materials (Adv. Funct. Mater. 38/2017). (10th October 2017) - Yang, Lei; Gong, Ze; Lin, Yuan; Chinthapenta, Viswanath; Li, Qunyang; Webster, Thomas J.; Sheldon, Brian W.
Abstract : In article number1702689, Lei Yang, Yuan Li, Brian W. Sheldon, and co‐workers report that cell filopodial extension on ultrastiff, disordered topography is governed by the contact between filopodial tip and surface asperities. Both experimental and modeling evidence reveal extension dynamics distinct from those reported on soft or ordered topographies and therefore provide key information to understand and design the biointerface of medical implants.